Chedi jiefa pipan "Sirenbang" jiqi zai Liaoningde neige dailirende taotian zuixing
'Thoroughly expose and criticize the neinous crimes of the "Gang of Four" and their representatives in Liaoning'. Anti-Gang of Four.